Investigation of adhesive wear properties of glass fiber reinforced polyester composites having different chemical compositions - İlhan, Recep; Feyzullahoglu, Erol (SAGE Publications Ltd, 2021)
Glass fiber reinforced polyester composite materials are widely used in various areas due to their high specific strength, low weight, excellent elasticity, high corrosion resistance, and high thermal stability. This study aims to investigate the effects of resin materials and various fillers and wear parameters such as different loads and speeds on the tribological properties of glass fiber reinforced polyester composite materials. In this experimental study, various resins (tensile additive orthophthalic polyester and plain orthophthalic polyester), fillers (alumina and glass beads), and reinforcing materials were used during the sample preparation. The samples were subjected to an adhesive wear test at two different speeds (n = 100 r/min and n = 200 r/min) and different loads (F = 10 N and F = 20 N) at 150 m sliding distance. The friction coefficient and friction force were measured by the tribometer. The thickness of the wear trace was later measured and the wear rate was calculated. Wear surfaces of samples were visualized with a three-dimensional laser profilometer in order to obtain surface topographies and surface roughness values. The sample surfaces were examined by scanning electron microscopy in order to understand the wear mechanisms and to characterize the morphology of worn surfaces. Experimental results have shown that alumina or glass beads fillers can reduce the average friction coefficient when used in the correct amounts. The use of glass bead filler in orthophthalic polyester resin with tensile additive is more effective than reducing the wear rate compared to alumina filler. The load on the wear behavior of glass fiber reinforced polyester composite materials is more effective than the speed.
Keywords: Adhesive wear; polyester; glass fiber; filler materials